Systematic design of particle dampers for horizontal vibrations with application to a lightweight manipulator. (13th October 2021) - Meyer, N.; Schwartz, C.; Morlock, M.; Seifried, R.
Abstract: Particle damping has become a favorable passive damping technique for lightweight structures, however, its complex dimensioning process hinder its wide use in technical applications. In this paper, a multilevel design tool chain is presented to enable a systematic design and dimensioning process of particle dampers. Thereby various numerical models and experimental tests are combined. This starts with investigations of the micro-mechanical behavior of single particle impacts. Continuing, with analyzing the properties of vibrated granular matters inside a container and ending with designing a damper for a desired structure. The good agreement of the models and their efficiency for the damper design and dimensioning are finally demonstrated on an elastic lightweight manipulator undergoing a horizontal, transient vibration. Using this design toolchain, a new and much more efficient damper design for low amplitude vibrations is introduced using the rolling attribute of spheres. By separating the particle damper into several layers, high damping of the elastic lightweight manipulator is achieved. Highlights: Development of a general design toolchain for particle dampers, enabling an efficient design. Introduction of a new damper design for low amplitude vibrations using the rolling attribute of spheres. Development of an analytical description for the energy dissipation. Numerical verification of the analytical formulation by means of the energy dissipation field. Experimental validation of both, the numerical and analytical model, by application to a horizontal transient vibrating lightweight elastic manipulator.